Synergy of Ecotourism Strategy, Conservation Awareness, and Social Participation in Supporting Forest Conservation and Ecological Stability - Asjulia Asjulia; Herawaty Herawaty; Dian Mitrnawaty Sultan; Putri Alifiah (Jurnal Wasian, 2026)
The Battang forest area in Palopo City faces ecological sustainability challenges due to pressure from human activities and low conservation awareness. Therefore, an integrated management approach combining ecotourism strategies, conservation awareness, and social participation is required to support forest conservation and ecological stability. This study aims to analyze the integrated role of ecotourism strategies, conservation awareness, and social participation in supporting forest conservation and ecological stability in the Battang area. The study used a quantitative approach with a survey method of 280 respondents consisting of members of forest farmer groups, local tourism actors, traditional leaders, and communities around the forest area. Data were analyzed using Structural Equation Modeling (SEM) to examine the relationships among variables. The results showed that conservation awareness (p = 0.000) and social participation (p = 0.000) significantly influenced forest conservation, while ecotourism strategies did not significantly influence (p = 0.193). However, all three independent variables significantly influenced ecological stability, with social participation as the most dominant factor (p = 0.000). The R² values of 0.779 for forest conservation and 0.810 for ecological stability indicate strong model predictive power. The findings indicate that conservation awareness and community participation are key drivers of forest conservation and ecological stability. Furthermore, the effectiveness of ecotourism initiatives depends strongly on social support and the presence of conservation-oriented values that encourage sustainable and non-exploitative resource use.